INTESTINAL PARASITES IN CHILDREN WITH NEUROLOGICAL DISORDERS TREATED AT A REHABILITATION INSTITUTION IN NITERÓI, Rio de Janeiro, BRAZIL - Torres de Freitas, Juliana; da Silva Matos, Juliana; Collino Scarabeli, Stephanie; Monteiro Fonseca, Ana Beatriz; da Silva Barbosa, Alynne; Machado Pereira Bastos, Otilio; Maria Antunes Uchôa, Cláudia (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Enteroparasitosis presents high prevalence in developing countries, and is frequent among children, and those with disabilities present even higher susceptibility. The present study evaluated 156 children with neurological disorders to whose parents or guardians an epidemiological questionnaire was applied with a view to identifying risk factors. Stool samples were processed using Ritchie modified by Young, Faust et al., Lutz and Baermann-Moraes techniques. Thirteen samples (8.3%) were positive, being Blastocystis sp. the most frequent parasite (46.2%). Higher positivity was observed for protozoa, especially non-pathogenic. A statistically significant association was only found between the educational level of the mother and positivity for enteroparasites. Among positive children, the habit of placing their hands and objects in their mouths and the consumption of raw vegetables was more frequent. The results show the existence of care and sanitation minimizing the acquisition of intestinal parasite diseases. It is important to alert parents and caregivers about personal hygiene, water and food quality, as well as the environment, considering that transmission of these parasites occurs via the fecal-oral route, in association with multiple factors.